Habits of the mind : intellectual life as a Christian calling - Sire, James W (Downers Grove, Ill. : InterVarsity Press, 2000)
*What is an intellectual? *How can you learn to think well? *What does it mean to love God with your mind? *Can the intellectual life be a legitimate Christian calling? *Is the intellectual life your calling? ... James Sire brings wit and wisdom to bear on these questions and their possible answers. And he offers an unusual "insider's view" of learning how to think well for the glory of God and for the sake of his kingdom. In Habits of the Mind Sire challenges you to avoid one of the greatest pitfalls of intellectual life--by resisting the temptation to separate being from knowing. He shows you how to cultivate intellectual virtues and disciplines--habits of mind--that will strengthen you in pursuit of your calling. And he offers assurance that intellectual life can be a true calling for Christians: because Jesus was the smartest man who ever lived, Sire argues, you can and should accept the challenge to think as well as you are able
Confessions of an intellectual wannabe -- John Henry Newman as an intellectual -- The perfection of the intellect -- How thinking feels : what is an intellectual? -- The moral dimension of the mind : what is a Christian intellectual? -- Perfecting the intellect : the intellectual disciplines -- Thinking by reading -- Jesus the reasoner -- The responsibility of a Christian intellectual
Includes bibliographical references (pages 225-256) and index
Keywords: Thought and thinking -- Religious aspects -- Christianity; Intellect -- Religious aspects -- Christianity